A Review of Clinical Data on Salvage Therapy in Spinal Cord Stimulation - Reddy, Rajiv D. (Neuromodulation, 2019)
BACKGROUND: Since its introduction in 1967, neuromodulation through spinal cord stimulation (SCS) or dorsal root ganglion stimulation (DRGs) has advanced significantly in both the technology and indications for use(1).There are now over 14,000 SCS implants performed worldwide every year(2). This review focuses on mechanisms behind the loss of efficacy in neuromodulation and current data on salvage therapy, defined as the conversion of a neuromodulation device to an alternative SCS or DRG stimulation, in the event of loss of efficacy or failure of a trial. STUDY DESIGN: A narrative review of clinical studies regarding habituation, explant data, and salvage therapy with SCS. METHODS: Available literature was reviewed on spinal cord stimulation technology and salvage therapy. Data sources included relevant literature identified through searches of PubMed, MEDLINE/OVID, SCOPUS, and manual searches of the bibliographies of known primary and review articles. OUTCOME MEASURES: The primary outcome measures were to understand the mechanisms of loss of efficacy, provide a review of explants due to failure in treatment, and summarize the data on current salvage therapy in SCS. RESULTS: A total of 8 studies and 4 abstracts/poster presentations were identified and reviewed. Of the 8 studies, only one was a randomized controlled trial. CONCLUSIONS: There is limited evidence for the appropriate treatment alternatives, but from data currently available the conversion from conventional tonic stimulation to burst, high frequency (10kHz), multiple wave forms, and/or DRGs may be appropriate in select patients and will require further research to determine the most appropriate first line salvage in the context of the underlying pain pathology.